2020
DOI: 10.3390/molecules25215162
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Quantification and Validation of Biomarker Scopoletin in Paederia foetida by qNMR and UV–Vis for Herbal Preparation

Abstract: Scopoletin has previously been reported as a biomarker for the standardization of Paederia foetida twigs. This study is the first report on the determination and quantification of scopoletin using quantitative nuclear magnetic resonance (qNMR) in the different extracts of Paederia foetida twigs. The validated qNMR method showed a good linearity (r2 = 0.9999), limit of detection (LOD) (0.009 mg/mL), and quantification (LOQ) (0.029 mg/mL), together with high stability (relative standard deviation (RSD) = 0.022%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Peak 5 and 6 exhibited closely related chromatographic and spectral features, which were in accordance with that of dicaffeoylquinic acid, and the two compounds were thus assigned to be isomeric compounds thereof. Peak 3 gave an UV absorbance spectrum similar to that of a 6,7-di-oxy-coumarin [ 41 ]. The base peak of the ESI+ spectrum was found to be the pseudomolecular ion at m / z 193 confirmed by the presence of [M+Na+H] + at m / z 215 and [M-H] − at m / z 191.…”
Section: Resultsmentioning
confidence: 99%
“…Peak 5 and 6 exhibited closely related chromatographic and spectral features, which were in accordance with that of dicaffeoylquinic acid, and the two compounds were thus assigned to be isomeric compounds thereof. Peak 3 gave an UV absorbance spectrum similar to that of a 6,7-di-oxy-coumarin [ 41 ]. The base peak of the ESI+ spectrum was found to be the pseudomolecular ion at m / z 193 confirmed by the presence of [M+Na+H] + at m / z 215 and [M-H] − at m / z 191.…”
Section: Resultsmentioning
confidence: 99%
“…10 Moreover, in different ingredients of churna and in composite churna a rapid, sensitive UV spectroscopic method was developed by using gallic acid as marker at 271nm and validated by different parameters as mentioned in ICH. 11 Furthermore, the other literature review revealed that there are various methods available for the detection and quantification of eugenol alone or along with other constituents using UV-spectroscopy, 12 High-performance liquid chromatography 13 and LC-MS. 14 Likewise, scopoletin was estimated by UV-spectroscopy, 15 HPTLC 16 and High-performance liquid chromatography. 17 Hence, from the literature review it is clear that there is no method reported in pharmacopoeias for simultaneous analysis of eugenol and scopoletin by UV spectroscopy in Avipattikar churna.…”
Section: Discussionmentioning
confidence: 99%
“…Substep seven: The yellow color was observed using the detector on exposure LED lamps as the modified Indonesia Patent Registered P00202107382 on September 9, 2021. The limit detection of RTD was evaluated based on the yellow color formation of the samples at the lowest concentrations of serial tetracycline dilutions [ 28 , 29 ]. Criteria of the color yellow and hypertext markup language code are as follows as presented in Figure-1 [ 30 - 32 ].…”
Section: Methodsmentioning
confidence: 99%